Analysis of 1997 coordinated portfolio investment survey results and plans for the 2001 survey. - International Monetary Fund. (Washington, DC : International Monetary Fund, 2000)
This analysis and plans presents an assessment of 1997 survey data and a summary of improvements introduced, as a result of countries' participation in the 1997 CPIS, into national systems for collecting data on international portfolio investment
Prepared by the IMF Statistcs Department.
"Intended to complement the Results of the 1997 Coordinated Portfolio Investment Survey"-- p. 7.
Includes bibliographical references (p. 79-80).
osc 1/09/2021
Loans
Keywords: Economic assistance; Debts, External; Loans, Foreign; Economic surveys; Economic forecasting